The Duration and Political Nature of the Inca Empire - Barker, Robert (The Edwin Mellen Press, 2014)
A fascinating resource on the evolution of the Inca Empire and, in particular, the creation of chronology and genealogy of the Inca dynasty. The work argues that the Incas, both as an ethnic group in the Cuzco region and as an empire, lasted a lot longer than presently thought.